The mutational pattern of primary lymphoma of the central nervous system determined by whole-exome sequencing - Vater, Inga; Russell, Robert B.; Eils, Roland (Leukemia, 2015)
To decipher the mutational pattern of primary CNS lymphoma (PCNSL), we performed whole-exome sequencing to a median coverage of 103 × followed by mutation verification in 9 PCNSL and validation using Sanger sequencing in 22 PCNSL. We identified a median of 202 (range: 139-251) potentially somatic single nucleotide variants (SNV) and 14 small indels (range: 7-22) with potentially protein-changing features per PCNSL. Mutations affected the B-cell receptor, toll-like receptor, and NF-κB and genes involved in chromatin structure and modifications, cell-cycle regulation, and immune recognition. A median of 22.2% (range: 20.0-24.7%) of somatic SNVs in 9 PCNSL overlaps with the RGYW motif targeted by somatic hypermutation (SHM); a median of 7.9% (range: 6.2-12.6%) affects its hotspot position suggesting a major impact of SHM on PCNSL pathogenesis. In addition to the well-known targets of aberrant SHM (aSHM) (PIM1), our data suggest new targets of aSHM (KLHL14, OSBPL10, and SUSD2). Among the four most frequently mutated genes was ODZ4 showing protein-changing mutations in 4/9 PCNSL. Together with mutations affecting CSMD2, CSMD3, and PTPRD, these findings may suggest that alterations in genes having a role in CNS development may facilitate diffuse large B-cell lymphoma manifestation in the CNS. This may point to intriguing mechanisms of CNS tropism in PCNSL.